The Spatiotemporal Pattern of Trauma in Victims of Violence Visited in Emergency Room of Rajaei Hospital, Shiraz, Iran - Rouhezamin, Mohammad Reza (Bull Emerg Trauma, 2013)
OBJECTIVE: To explain an important aspect of violence, the spatiotemporal pattern of trauma in victims of violence visited in emergency room of Rajaei hospital, Shiraz, Iran METHODS: This cross-sectional prospective study comprised 109 randomly selected victims of violence visited in emergency room of Rajaei hospital, a tertiary referral hospital affiliated to Shiraz University of Medical Sciences in winter 2013. We recorded the demographic information as well as data regarding the type and time of the injuries. The data collected for each victim was then entered in a data gathering form. RESULTS: The study included 88% males with mean age 27.8 ± 8.8 years, which encompassed more than 60% young adults. Our study showed a temporal pattern with triple peaks. Moreover, 64% of assault trauma occurred at night. Furthermore, our study showed the majority of our patients suffered from stab wounds and about 57% of patients studied lacked high school diploma. Moreover it was revealed that violence was more common in downtown Shiraz, especially in the Fifth city district with simultaneous presence of many risk factors for violence. CONCLUSION: The result of this study showed that age, gender, educational status and temporal peak of violence were shown to be similar to other investigations conducted  in other countries. Despite these similarities, stabbing were more prevalent in our study. Additionally, the Fifth city district of Shiraz seems to be the main city district where preventive intervention is needed to reduce violence- related injuries.